Running Dictation as an Effective Technique on the Teaching Writing Skill - Fitri Nurdianingsih; Oktha Ika Rahmawati (English Language and Literature International Conference (ELLiC) Proceedings, 2018)
Writing is an activity to tell our ideas and thought about something in written form. Writing becomes an important skill to be mastered by the students to face the global era. It conveys that writing is used in every aspect of life, particularly for interacting and communicating with other people. Writing can be the most difficult thing to do because sometimes it is difficult to decide the words or even to produce a paragraph. One of the techniques that can be used in teaching writing is running dictation. Running dictation is a technique of dictation method that can be used for teaching writing cooperatively. It is a fun technique that can be adapted in a number of ways and it is fairly easy to prepare, explain, set up, and adaptable. Using running dictation to teach writing can avoid boredom for students because the technique help the students to brainstorm, elaborate paragraph and finish final paragraph. The objective of this study is to know whether or not the implementation of running dictation technique could be an effective technique in teaching writing skill. The method used in this study was an experimental research. The data collecting technique by using writing test to measure the students’ achievement. The data analysis technique by using t-test formula. This study compared between pre and post treatment which is using running dictation technique. The implementation of running dictation technique can improve students’ writing, memorizing, communicating cooperatively with their group and of course it can improve students’ creativity during teaching and learning process. Besides that, running dictation technique motivates the students to encourage the students to improve their writing skill. Finally, this technique gives good contribution and had a positive effects in improving the students’ writing skill achievement.